Analysis of nucleoid‐associated protein‐binding regions reveals DNA structural features influencing genome organization in Mycobacterium tuberculosis. Issue 19 (27th August 2021) - Sarkar, Sharmilee; Dey, Upalabdha; Khohliwe, Trust Boitumelo; Yella, Venkata Rajesh; Kumar, Aditya
Abstract : Nucleoid‐associated proteins (NAPs) maintain bacterial nucleoid configuration through their architectural properties of DNA bending, wrapping, and bridging. However, the contribution of DNA structural alterations to DNA‐NAP recognition at the genomic scale remains unresolved. Present work dissects the DNA sequence, shape and altered structural preferences at a genomic scale for six NAPs in Mycobacterium tuberculosis . Results suggest narrower minor groove width (MGW) and higher DNA rigidity are marked for the binding sites of EspR and Lsr2, while mIHF, MtHU and NapM have heterogeneous DNA structural predilections. In contrast, WhiB4–DNA‐binding sites were characterized by wider MGW, highly deformable and less curved DNA. This work provides systematic insight into NAP‐mediated genome organization as a function of DNA structural features. Abstract :